Viral infections and global change - Singh, Sunit K. (Hoboken, New Jersey : Wiley, 2014)
A timely exploration of the impact of global change on the emergence, reemergence, and control of vector-borne and zoonotic viral infections From massively destructive ""superstorms"" to rapidly rising sea levels, the world media is abuzz with talk of the threats to civilization posed by global warming. But one hazard that is rarely discussed is the dramatic rise in the number and magnitude of tropical virus outbreaks among human populations. One need only consider recent developments, such as the spread of chikungunya across southern Europe and dengue in Singapore, Brazil, and the so.
Includes bibliographical references and index.
Online resource; title from digital title page (Wiley, viewed on Nov. 13, 2013).
Keywords: Virus diseases -- Transmission; Virus diseases -- Environmental aspects; Global warming -- Health aspects; Globalization -- Health aspects; Virus Diseases -- diagnosis; Virus diseases; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Virus Diseases -- transmission; Environment; Global Warming; Internationality; Electronic books